Species of Fungi and Pollen in the PM1 and the Inhalable Fraction of Indoor Air in Homes - Rui Lu; Ann Dorte Pørneki; Jonas N. Lindgreen; Yanpeng Li; Anne Mette Madsen (Atmosphere, 2021)
Airborne microbial fragments in the PM1 fraction (particles with aerodynamic diameters less than 1 µm) are a cause for concern as they may potentially deposit in the alveoli of the human airways. This study aimed to use qPCR to identify and quantify 24 different species or groups of genera in the PM1 and the inhalation fraction (particles that may enter the mouth or nose during breathing) of indoor air and to relate this to what has previously been found for each species. Results showed that eight fungal species, and Aspergillus/Penicillium/Paecilomyces variotii, as well as Alnus/Corylus and actinobacteria belonging to the Streptomyces genus were detected both in the PM1 and the inhalable fraction. Five fungal species were only detected in the inhalable fraction. A significant effect of season was found on the fungal composition in the PM1 (p = 0.001) and the inhalable (p = 0.017) fraction. This study demonstrated that it is possible to use qPCR to identify and quantify different microbes in the PM1 fraction, and it has improved our understanding of the qualitative and quantitative relationship between the PM1 and the inhalable microbial particles in indoor air. Combined with the literature review it also shows a large variation within and between species in the share of fungi which is present as fragments.